Carriage of vancomycin-resistant Enterococcus faecium in infants following an outbreak in the neonatal intensive care unit: time to clearance of carriage and use of molecular methods to detect colonization. (31st March 2023) - Schechner, Vered; Lellouche, Jonathan; Stepansky, Sarit; Mandel, Dror; Grisaru-Soen, Galia; Wullfhart, Liat; Schwartz, David; Carmeli, Yehuda
Abstract: Among 46 infants colonized with vancomycin-resistant Enterococcus faecium during an outbreak in a neonatal intensive care unit, the estimated time until half had achieved clearance was 217 days. All 40 infants who completed follow-up cleared carriage by 1 year. No predictors of prolonged carriage (> 6 months) were identified.